The The Effect Of Rice Price and Population On Rice Consumption In Java, Sumatra, and Bali 2020-2024: English - Ilman Nafi Muhammad; Lucky Rachmawati (Universitas Negeri Surabaya, 2026)
This study aims to analyze how rice prices and population size affect rice consumption in Java, Sumatra, and Bali. The study covers 13 regions in Sumatra, Java, and Bali from 2020 to 2024. Rice is a strategic commodity that plays an important role in national food security. Therefore, it is necessary to understand rice prices, population, and rice consumption in order to formulate strategic and effective policies. The research method used is quantitative with an associative approach and panel data regression using a fixed effect model with the help of Stata 14.2 software. The results show that rice prices and population have a significant and positive effect on rice consumption in Sumatra, Java, and Bali. The findings of this study have the potential to serve as a reference, especially for the government and Bulog in formulating strategic and effective policies regarding food security for Indonesia, particularly in the regions of Java, Sumatra, and Bali.